PERANAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) DALAM MENGELOLA BELANJA BANTUAN SOSIAL (Studi Kasus pada Pemerintah Daerah Kabupaten Aceh Tengah) - , HERMAN DELLI; , Prof. Dr. Bambang Riyanto, LS., M.B.A., Ak., C.M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Government Internal Control System (SPIP) stipulated in Government Regulation No. 60 of 2008 is a control system that is set up to assist the implementation of the tasks and functions of government agencies who held government affairs and public administration at both central and local levels. SPIP is a manifestation of the formation of the implementation of the mandate of Law No. 1 of 2004 on State Treasury, namely Article 58 paragraph (2). Besides publishing SPIP is a form of adjustment of the latest developments is the conception of the internal control of the hard control becomes soft control and is expected to increase the effectiveness of controls to identify risks in achieving objectives. Social assistance is the assistance provided by the local government to the community which aims to overcome the social risks faced by the community. Social assistance should theoretically be able to help people in improving the well-being so that they can live a decent and reasonable that the main program of government in combating poverty. Nevertheless, the phenomenon that occurs is not always in line with the objectives of the essentials. The number of cases of abuse of social assistance that happens has hindered the achievement of the goal of social assistance itself. There are many factors that lead to the abuse of social assistance in the area, one of which is the problem of personnel resources manager of social assistance expenditure both in terms of understanding of the regulatory, ethical, and other sebaginya. With conditions like these we need a control system to achieve the objectives of social assistance is good, transparent, and accountable. This research was conducted in Central Aceh District Government by using the method of collecting data through interviews and documentation. The results showed that there are some risks in managing social assistance expenditure that could potentially hinder the achievement of the objectives of social assistance.